How digital environments in schools might be used to boost social skills: Developing a conditional augmentation hypothesis. (November 2018) - McNaughton, Stuart; Rosedale, Naomi; Jesson, Rebecca Ngaire; Hoda, Rashina; Teng, Lin Sophie
Abstract: The use of online devices, tools and technologies in schools is seen as being able to promote '21st century' skills, specifically inter personal (e.g., being empathetic, taking others' perspectives, cooperation and collaboration) and intra personal skills (e.g., persistence and self-control). We review theoretical rationales for and, where available, research evidence about the impact of digital tools and technologies on the development of these skills under two conditions. One is where there are direct effects of access to and use of digital technologies relatively independently from other influences of the teacher. The evidence suggests powerful mechanisms are afforded directly, such as feedback, social learning, agentive learning and play (game-based learning), but that effects are variable and there are both positive and negative influences on skills. The second condition is when the digital environments are mediated by teaching. The evidence is that both effectiveness and the consistency of effects of digital environments depend on the deliberate design and management of the tools and their functions. Explanations relate to the mediating effects of the activity structures and how they are designed, the role of the teacher in both that design and specific instructional acts, and the guided actions of interlocutors through digital devices. We propose a teacher 'conditional augmentation' hypothesis: teachers' augmentation adds instructional power to the direct effects of digital technologies. Highlights: We review theoretical rationales for and research evidence about the impact of digital tools on social skills. Powerful mechanisms are afforded directly such as feedback, social learning, agentive learning and game-based learning. Effectiveness of digital environments depends on the deliberate design and management of the tools and their functions. We propose a conditional hypothesis: teachers' augmentation adds instructional power to the direct effects of digital tools.